Reelin Signaling, Hippocampal Neurogenesis, and Efficacy of Aspirin Intake & Stem Cell Transplantation in Aging and Alzheimer’s disease - Shetty, Ashok K. (JKL International LLC, 2010)
Comprehending the mechanisms underlying the pathophysiology of aging and Alzheimer’s disease has immense value for developing strategies that promote successful aging and prevent or cure Alzheimer’s disease. The first issue of the new journal, “Aging & Disease” comprises articles that discuss the current knowledge pertaining to changes in reelin signaling in normal & pathological forms of aging, memory and neurogenesis in Aging & Alzheimer’s disease, the efficacy of a non-steroidal anti-inflammatory drug aspirin in combination with docosahexaenoic acid for reducing the risk for Alzheimer’s disease, and the usefulness of stem cell transplantation for improving memory in aging and Alzheimer’s disease. The highlights and the importance of the above issues to Aging and Alzheimer’s disease are discussed in this commentary.